Antinociception Induced by Copper Salt Revisited: Interaction with Ketamine in Formalin-Induced Intraplantar and Orofacial Pain in Mice - Hernandez-Kunstmann, A; Morales-Munoz, B; Constandil-Cordova, L (Quintessence Publishing Co. Inc., 2018)
Aims: To evaluate in mice the antinociceptive effect of copper in spinal and trigeminal nociceptive pathways by using the intraplantar and orofacial formalin tests, respectively, and to examine whether this effect may interact synergistically with ketamine-induced antinociception. Methods: Nociceptive behaviors (licking/ biting of the formalin-injected limb and rubbing/scratching of the formalin-injected orofacial area) in male mice were evaluated during a 45-minute observation period post-formalin injection. Dose-response curves for intraperitoneal (ip) copper sulfate and ketamine allowed their combination in equi-effective doses, and their interaction was determined with isobolographic analysis. The results were examined with one-way analysis of variance followed by the Bonferroni post hoc test. Significance was accepted at an alpha level of .05. Results: Irrespective of the region injected with formalin (upper lip or hindlimb), copper sulfate (0.3, 1.0, and 3.0 mg/kg) and ketamine (1.0, 3.0, and 10 mg/kg) dose-dependently decreased the nociceptive behaviors evoked by formalin injection. Isobolographic analysis showed a superadditive interaction between copper and ketamine at the spinal level, but this interaction was only additive at the trigeminal level. Conclusion: The results suggest that copper salts could be used to synergistically improve the efficacy of some commercial centrally acting analgesic agents, such as ketamine, while reducing the possibility of side effects. However, a synergistic effect probably should not be expected if treatment is for orofacial pain. © Quintessenz.